Morphological characteristics, chemical composition and antioxidant activity of seeds by four wild Opuntia species from North of Mexico - Núñez-Gastélum, José Alberto (2018)
Morphological characteristics and chemical composition of seeds of four species of Opuntia genus endemic to the Samalayuca Valley were evaluated in this study. Morphology and chemical composition of the four species were clearly different. Seeds of O. polyacanta var. arenaria presented the highest values of area, length and width. However, O. phaeacantha showed the highest values in palmitoleic acid (1.34 ± 0.12%), stearic acid (5.60 ± 0.47%), oleic acid (19.42 ± 1.04%), alpha linolenic acid (2.42 ± 0.33%), arachidic acid (0.61 ± 0.11%), and eicosenoic acid (1.74 ± 0.36%); but, this species showed the lowest values in linoleic acid (54.35 ± 2.91 %) content. In conclusion, seeds of O. phaeacantha could be an important new source of health-promoting polyunsaturated fatty acid, and its use in arid and semi-arid regions should be encouraged.